Malawi - Munthali, Kondwani Bell (London : Kuperard, 2018)
"Culture smart! Malawi" is an illuminating and practical guide to Malawi's culture and society. It wll help you turn your visit-- whether it's for business or for pleasure-- into a memorable and enriching experience. Contents include: local customs and traditions; the impact of history, religion, and politics; the Malawians at home, work, and play; eating and drinking, Malawi style; dos, don'ts, and taboos; business practices; communication, spoken and unspoken; and many practical tips for managing the unexpected"--Cover, page 4.
Includes bibliographical references (page 165) and index.
Keywords: Etiquette -- Malawi -- Handbooks, manuals, etc; Visitors, Foreign -- Malawi -- Life skills guides; Malawi -- Guidebooks; Guidebooks; Handbooks and manuals; Life skills guides